Transitional Safeguarding: A Strategic Response. Issue 1 (1st January 2022) - Walker-McAllister, Siân; Cooper, Adi
Abstract : This paper provides an overview of the new safeguarding governance arrangements introduced in Bath & NE Somerset (B&NES), outlining how a Transitional Safeguarding approach is being addressed. B&NES merged the governance arrangements for the Local Safeguarding Children's Board (LSCB) with the Safeguarding Adults Board (SAB) and Community Safety Partnership (CSP). The primary driver for this was to create an all-encompassing life course approach to the governance of safeguarding in B&NES, through joined up leadership at a strategic level. The aim was to reduce duplication of effort from all safeguarding partners and to ensure that partners were able to prioritise the most effective approach to deliver better joined up services, particularly at the transition points across services, to reduce gaps in provision. Analysis and evaluation of this approach provides evidence that improved delivery of effective governance is beginning to have a positive impact on how services are delivered to support young people, particularly around how Transitional Safeguarding methods are used across Children's and Adult Services to meet the needs of young people.